ZASP interacts with the mechanosensing protein Ankrd2 and p53 in the signalling network of striated muscle. - Valentina C Martinelli (Public Library of Science (PLoS), 2014)
ZASP is a cytoskeletal PDZ-LIM protein predominantly expressed in striated muscle. It forms multiprotein complexes and plays a pivotal role in the structural integrity of sarcomeres. Mutations in the ZASP protein are associated with myofibrillar myopathy, left ventricular non-compaction and dilated cardiomyopathy. The ablation of its murine homologue Cypher results in neonatal lethality. ZASP has several alternatively spliced isoforms, in this paper we clarify the nomenclature of its human isoforms as well as their dynamics and expression pattern in striated muscle. Interaction is demonstrated between ZASP and two new binding partners both of which have roles in signalling, regulation of gene expression and muscle differentiation; the mechanosensing protein Ankrd2 and the tumour suppressor protein p53. These proteins and ZASP form a triple complex that appears to facilitate poly-SUMOylation of p53. We also show the importance of two of its functional domains, the ZM-motif and the PDZ domain. The PDZ domain can bind directly to both Ankrd2 and p53 indicating that there is no competition between it and p53 for the same binding site on Ankrd2. However there is competition for this binding site between p53 and a region of the ZASP protein lacking the PDZ domain, but containing the ZM-motif. ZASP is negative regulator of p53 in transactivation experiments with the p53-responsive promoters, MDM2 and BAX. Mutations in the ZASP ZM-motif induce modification in protein turnover. In fact, two mutants, A165V and A171T, were not able to bind Ankrd2 and bound only poorly to alpha-actinin2. This is important since the A165V mutation is responsible for zaspopathy, a well characterized autosomal dominant distal myopathy. Although the mechanism by which this mutant causes disease is still unknown, this is the first indication of how a ZASP disease associated mutant protein differs from that of the wild type ZASP protein.